Effect of Nocturnal Intermittent Peritoneal Dialysis on Intraocular Pressure and Anterior Segment Optical Coherence Tomography Parameters - Chong, K.L.; Samsudin, A.; Keng, T.C.; Kamalden, T.A.; Ramli, N. (Lippincott, Williams & Wilkins, 2016)
Purpose: To evaluate the effect of nocturnal intermittent peritoneal dialysis (NIPD) on intraocular pressure (IOP) and anterior segment optical coherence tomography (ASOCT) parameters. Systemic changes associated with NIPD were also analyzed. Methods: Observational study. Nonglaucomatous patients on NIPD underwent systemic and ocular assessment including mean arterial pressure (MAP), body weight, serum osmolarity, visual acuity, IOP measurement, and ASOCT within 2 hours both before and after NIPD. The Zhongshan Angle Assessment Program (ZAAP) was used to measure ASOCT parameters including anterior chamber depth, anterior chamber width, anterior chamber area, anterior chamber volume, lens vault, angle opening distance, trabecular-iris space area, and angle recess area. T tests and Pearson correlation tests were performed with P<0.05 considered statistically significant. Results: A total of 46 eyes from 46 patients were included in the analysis. There were statistically significant reductions in IOP (-1.8±0.6 mm Hg, P=0.003), MAP (-11.9±3.1 mm Hg, P<0.001), body weight (-0.7±2.8 kg, P<0.001), and serum osmolarity (-3.4±2.0 mOsm/L, P=0.002) after NIPD. All the ASOCT parameters did not have any statistically significant changes after NIPD. There were no statistically significant correlations between the changes in IOP, MAP, body weight, and serum osmolarity (all P>0.05). Conclusions: NIPD results in reductions in IOP, MAP, body weight, and serum osmolarity in nonglaucomatous patients.